2018
DOI: 10.5546/aap.2018.eng.e649
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal evaluation in colchicine-treated familial Mediterranean fever patients with chronic abdominal pain: Cases series

Abstract: The aim of the study to evaluate familial mediterranean fever (FMF) patients with chronic abdominal pain unresponsive to colchicine treatment. Forty-eight patients who diagnosed in our Pediatric Rheumatology clinics and suffering from abdominal pain despite colchicine treatment were include. All patients were referred to a pediatric gastroenterologist. The pain characteristics such as onset, duration and frequency were recorded; gastrointestinal (GI) endoscopy was planned for differential diagnosis. MEFV mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Even normal EGDs performed appropriately will positively impact the management of paediatric patients. In our population, patients with FMF comprised a high percentage of patients with chronic abdominal pain that may have presented atypically;19 20 thus, we performed EGD to rule out other causes of chronic abdominal pain. Thomson et al 21 reported that 45% of the patients had a contributive yield due to EGD findings.…”
Section: Discussionmentioning
confidence: 99%
“…Even normal EGDs performed appropriately will positively impact the management of paediatric patients. In our population, patients with FMF comprised a high percentage of patients with chronic abdominal pain that may have presented atypically;19 20 thus, we performed EGD to rule out other causes of chronic abdominal pain. Thomson et al 21 reported that 45% of the patients had a contributive yield due to EGD findings.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine has been used in gout, familial Mediterranean fever disorders, osteoarthritis (Akman 2018;Alarcón 1981;Aran 2011;Das 2002;Halabe-Cherem 2009;Kiraz 1998;Lazaros 2018;Liantinioti 2018;Meneses 2015;Nuki 2008;Plotz 2021;Richette 2010;Vilardell 1978), dermatological disorders (Kaur 2020;Fujii 2021;Micheletti 2020;Zhao 2021), urological disorders (Sinanoglu 2018;Akman 2011;Ibrahim 2019), hepatology (Gong 2004;Rambaldi 2001), respiratory medicine , gastroenterology Rajapakse 2001;Verne 1997), and from secondary prevention of cardiovascular outcomes (Fiolet 2020;Imazio 2005;Imazio 2005a;Imazio 2014a;Maisch 2004;Nidorf 2013;Roubille 2020;Siak 2021;Tardif 2019;Xia 2021). The effect of colchicine is unique since it binds to unpolymerized tubulin heterodimers, forming a stable complex that effectively inhibits microtubule dynamics, not affecting the glucocorticoid signaling pathway as well arachidonic acid metabolites production and signal transduction (Deftereos 2013 ).…”
mentioning
confidence: 99%